Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Manipulasi Informasi Elektronik Dalam Transaksi Transportasi Online : Studi Putusan Nomor 143/Pid.B/2018/PN. Lmg - Barry Sugiarto; Ediwarman Ediwarman; Muhammad Hamdan; Jelly Leviza (Universitas Sumatera Utara, 2019)
Abstract. Existing online transportation services namely online taxis and online motorcycle taxis where online transportation uses smartphone technology to connect consumers with available drivers near the consumer's position, with the existence of this online transportation business not only benefits consumers but also benefits drivers, but the benefits the driver has resulted in many people registering as online transportation partners, this makes high competition between online transportation drivers. The high competition among drivers makes some drivers try to justify various ways to overcome the competition in order to continue to benefit where some drivers do is to do illegal access, which is the activity of manipulating or hacking the work system of online-based transportation applications to reap profits without having to deliver passengers so that they still get incentives from the online transportation company. The issues raised in this study, namely how the regulation of criminal law against the criminal acts of manipulation of electronic information in online transportation transactions, criminal liability for the perpetrators of the manipulation of electronic information in online transportation transactions based on Lamongan District Court Decree Number 143/Pid.B/2018/PN.Lmg, and law enforcement efforts against the crime of manipulation of electronic information in online transportation transactions, especially in the Decision of the Lamongan District Court Number 143/Pid.B/2018/PN.Lmg. To find answers to these problems, this research uses descriptive analytical normative legal research, in which normative legal research uses secondary data as the main data using data collection techniques carried out by library research, and data analysis uses qualitative data analysis methods. Keywords: criminal liability, manipulation, information, electronic data.